Genetic (co) variance across age of fiber diameter and standard deviation in Huacaya alpacas, estimated by repeatability, multi-trait and random regression models - Cruz, Alan (2020)
Universidad Nacional Agraria La Molina. Escuela de Posgrado. Maestría en Producción Animal